Climatic Design of Iranian Traditional Buildings Case Study: Tabriz - Neghabi, Mahboobe (IJRDO-Journal of Applied Science, 2016)
Today, the environment, saving fossil energy and sustainable development have become important and common discussions at the international level. So that energy sources’ conservation, avoiding contaminating the land and the environment, reducing the amount of fossil energy consumption and coexistence with natural and climate conditions have become one of the most important measures in architecture and urbanism. In modern discussions of sustainable architecture, the use of passive systems for cooling and heating of buildings is a way of saving energy consumption. On the other hand, Iran’s traditional architecture in the residential sector and in the non-residential sector, as well as the integration of these two broadly in the name of the city has unique features that while considering aesthetic issues and the environment conservation has also been responsive to climate needs of each region. Techniques and rules used in this architecture have many new concepts in the field of sustainable architecture in itself clearly that the paper examined these concepts in Tabriz residential architecture located in cold regions of Iran. The method of the present paper is descriptive-analytic and data collection method is library and field. In this paper, the traditional solutions for cooling and heating in traditional architecture were classified in the form of passive cooling and heating methods and finally the result was that most of proposed methods have been considered in passive systems of traditional architecture and by detailed study of Iran architecture, urban development and modernization intelligent solutions can be found matching local architecture of regions.